Measuring anterior trunk deformity in scoliosis: development of asymmetry parameters using surface topography (a pilot study). Issue 2 (October 2016) - Knott, Patrick; Lonner, Baron; Smith, Mark; Frommeyer, Erin; Ren, Yuan
Abstract Background Clinicians who assess and treat patients for scoliosis typically use parameters that are all visible from the posterior view. Radiographs assess the internal spinal deformity, but do not directly evaluate body shape, either posterior or anterior. This is problematic, as the patient is most concerned about the way they appear in the mirror. An objective set of anterior measurements is needed to help quantify the anterior asymmetry that is present in scoliosis. Methods The design of this system of assessment was developed as a consensus of thinking from four points of view. A spine surgeon provided the musculoskeletal structural perspective. A plastic surgeon specializing in breast reconstruction provided the aesthetic and soft tissue perspective. A surface topography researcher provided the imaging perspective, and a scoliosis patient provided the self-perception and emotional perspective. Using an iterative process, a series of potential measurement parameters using surface topography measurements were considered, debated, and ultimately selected to be part of a system of measurement that provides an overall assessment of anterior trunk asymmetry. Results An anterior surface topography scan in the relaxed, standing position was taken of the scoliosis patient. The computer provides a 3D topographical model that is used to complete measurements that can be combined to achieve an Anterior Aesthetic Deformity Score. Shoulder parameters, including shoulder height difference and shoulder slope difference, make up 40 % of the total score. Breast asymmetry, including nipple height difference and sternal notch-to-nipple distance, make up 30 % of the total score. Waist asymmetry makes up the final 30 % of the score, providing an objective and quantifiable measure of anterior trunk deformity. Conclusions These measurements provide an objective, systematic evaluation of anterior trunk asymmetry that can be used in the assessment of patients with scoliosis. Clinical research should now be done to validate this system and show that it is reproducible in a variety of settings and patients.